2002
DOI: 10.1002/joc.810
|View full text |Cite
|
Sign up to set email alerts
|

Links between circulation and changes in the characteristics of Iberian rainfall

Abstract: Investigation of the links between atmospheric circulation patterns and rainfall is important for the understanding of climatic variability and for the development of empirical circulation-based downscaling methods. Here, spatial and temporal variations in circulation-rainfall relationships over the Iberian Peninsula during the period 1958-97 are explored using an automated circulation classification scheme and daily rainfall totals for 18 stations. Links between the circulation classification scheme and the N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
245
1
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 295 publications
(270 citation statements)
references
References 53 publications
20
245
1
4
Order By: Relevance
“…Alpert et al (2002) use the rainfall intensity for different categories or classes in the Mediterranean area and find that, in Spain, the trends for the extreme classes (light and heavy rains) are positive, whereas the central classes (moderate rains) show significant decreases. The results of Goodess and Jones (2002) for the Iberian Peninsula show a tendency towards more, less-intensive rain across much of Iberia, with a tendency towards days of increasingly intensive rain along the southeastern Mediterranean coast. Brunetti et al (2000Brunetti et al ( , 2001 detected positive trends for rainfall intensity for several gauges in northeastern Italy.…”
Section: Time Trendsmentioning
confidence: 93%
“…Alpert et al (2002) use the rainfall intensity for different categories or classes in the Mediterranean area and find that, in Spain, the trends for the extreme classes (light and heavy rains) are positive, whereas the central classes (moderate rains) show significant decreases. The results of Goodess and Jones (2002) for the Iberian Peninsula show a tendency towards more, less-intensive rain across much of Iberia, with a tendency towards days of increasingly intensive rain along the southeastern Mediterranean coast. Brunetti et al (2000Brunetti et al ( , 2001 detected positive trends for rainfall intensity for several gauges in northeastern Italy.…”
Section: Time Trendsmentioning
confidence: 93%
“…This has been applied in several regions such as the United Kingdom Wilby et al, 1995;Jones et al, 1993), USA (Wilby and Wigley, 1997), Scandinavia (Linderson, 2001) and Japan (Wilby et al, 1998). In the Iberian Peninsula, it has been widely used to classify weather types (Martín-Vide, 2002;Goodess and Palutikof, 1998;Goodess, 2000;Goodess and Jones, 2002;Trigo and DaCamara, 2000;Rasilla et al, 2002;Spellman, 2000a,b).…”
Section: Analysis Of the Temporal Variability Of The Winter Atmosphermentioning
confidence: 99%
“…Nevertheless, the complex relief that characterises the Iberian Peninsula and the maritime influence can modulate these influences spatially. In the Mediterranean coastland, different authors have shown that flows from east, and cyclonic weather types have an important role in precipitation (Romero et al, 1999;Goodess and Jones, 2002). Moreover, the flows from east can be reactivated because of hot conditions in the sea-surface temperature, which is frequent in autumn and early winter (Martín-Vide and Llasat, 2000;Serra et al, 1996;Millán et al, 1995).…”
Section: Influence Of Weather-type Frequency On Drought Spatial and Tmentioning
confidence: 99%
See 2 more Smart Citations